Diversity of Mosquito Species (Diptera: Culicidae) as An Effort to Control Disease Vectors in Cattle in Amun Kay Village, Tanah Miring District, Merauke - Desmina Kristiani Hutabarat; Apri Irianto; Maria M. Nay Lesik; Irine Ike Praptiwi; Yolanda Gebse (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Amun Kay Village is one of the villages in Tanah Miring District developed into an agricultural center with a background of transmigrant people working as farmers and cattle breeders. This village is located in a lowland area dominated by open shrub areas, rice fields, and swamps. Swamp areas, agricultural fields, and cattle areas become breeding sites for various types of mosquitoes. This study aims to find out about the different kinds of mosquitoes that live in Amun Kay village, Tanah Miring District, so that programs that take care of and maintain animals, like cattle, can better control the mosquitoes that spread disease to cattle. We adjusted the cattle collection method to the specific conditions of the research location. Based on the results of mosquito collection in 3 cattle cages in Amun Kay village, 32 mosquito species with 9 genera were found. The diversity of mosquito species in this study was moderate, and the evenness index of mosquito species was high. The low mosquito dominance index indicates that few mosquitoes dominate an area around the cattle barns in Amun Kay Village, Tanah Miring District, Merauke